(untitled) (National Administration Journal, 2022)
The purpose of this research was to know if the leadership style is related to each generation and if generational differences influence the preference or perception of their leaders; Taking as a case study a financial institution located in the province of Imbabura in Ecuador, using as an instrument the Multifactorial Leadership Questionnaire MLQ, which was applied to 61 employees. The results showed that the predominant leadership is transformational, the generation that prevails is the Millennial; the type of leadership and the generations are not related because the preference was concentrated on transformational leadership regardless of the generation to which the staff belonged, finally, the predominant type of leadership achieves results based on effectiveness, satisfaction and effort in people extra, without relating the generation to which they belong; that is, the leader’s behaviors obtain a response from the two generations present in the agencies. JEL Classification: J24, M12, M54